Scrutinization of Polystyrene Microsphere-grafted Multiwalled Carbon Nanotube and Silver Nanoparticle-based Hybrids: Morphology, Thermal Properties, and Antibacterial Activity. Issue 2 (22nd January 2017) - Akram, Zikra; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: Polystyrene microsphere (emulsion polymerization) was grafted on pure multiwalled carbon nanotube and amine-modified multiwalled carbon nanotube. Silver nanoparticle was also decorated on nanotube using chemical reduction (dimethylformamide). Amine-modified multiwalled carbon nanotube secures better silver attachment on nanotube wall. Polystyrene/Ag–amine-modified multiwalled carbon nanotube depicted fine dispersion in polymer latex due to modification. The 10% decomposition temperature and maximum degradation temperature of polystyrene/Ag–amine-modified multiwalled carbon nanotube was increased to 352 and 424°C. Antibacterial properties of nanocomposite were studied against respiratory track demolishing Gram-positive Staphylococcus aureus bacteria and two Gram-negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ). Ag nanoparticle was found responsible to potential death rate of microbes. GRAPHICAL ABSTRACT: